Symbolic Meanings of "Water" and “Path” in the Book of Proverbs - Nadeak, Ave Lucia; Bram, Barli (Language Circle: Journal of Language and Literature, 2024)
Symbolic meanings, which can be objects or words, can have varying meanings depending on the context. This research aims to determine the frequency of words containing the words "Water" and "Path" in the book of Proverbs and their symbolic meanings. Using qualitative methods and document analysis, the author compares the meanings of these words through context using Mishler's (1979) theory. In this research there are two problem formulations, namely 1) What is the frequency of words containing the words "Water" and "Path" in the book of Proverbs? 2) What are the symbolic meanings of the words "Water" and "Path" used in the book of Proverbs? The results show that the word "Water" appears 14 times and "Path" 13 times in the book of Proverbs, which often discusses sound guidance for individuals to make their path right and acceptable to God the Almighty. The research results can assist readers in understanding the meaning of these words when reading the book of Proverbs, a rare area of research on symbolic meanings.